Features of change of condition of a biogeometrical profile of bearing of students in the course of physical education - Лопацький, Сергій (Slobozhanskyi Herald of Science and Sport, 2016)
Sergey Lopacki Purpose: to study features of condition of a biogeometrical profile of bearing of students in the course of physical education. Material & Methods: 401 studentsof the 1–4 courses who are studied on a day form of education took part in the research. The following methods of research were used for the performance of the given tasks: analysis of scientific and methodical literature and documentary materials; pedagogical supervision; pedagogical experiment (carrying out the stating experiment) visual screening of condition of a biogeometrical profile of bearing [7]; methods of mathematical statistics. Results: it is established during the research, on the basis of visual screening that 74% of students had violations of bearing, and the largest number among them was made by students with scoliotic bearing. Tendencies and statistically reliable distinctions are established in values of assessment of condition of a biogeometrical profile of bearing of students in the direction of their reduction from course to course. The obtained data confirm the existence of the process of aggravation of symptoms of bearing of students. Conclusions: the obtained data will be used at the scientific foundation and development of technology of correction of violations of bearing of students in the course of physical education taking into account the level of condition of their biogeometrical profile.